HSN—helping in mental distress: a new emotion focused psychological first aid program - Scheele, Marina; Appel, Sandra; Rausch, Isabelle; Schecklmann, Martin; Klein, Jakob; Staudinger, Susanne; Schmidt, Roger; Kreuzer, Peter M.; Langguth, Berthold (Frontiers in Public Health, 2025)
Psychological first aid programs aim to train lay people to help others who are experiencing a mental health crisis or developing mental health problems. The current article introduces the new German psychological first aid training program HSN. The acronym HSN stands for “Helfen in Seelischer Not” (helping in mental distress) but also for the action chain “hear, speak, network.” The HSN program differs from other well-examined mental health first aid programs by (1) focusing primarily on emotions instead of disorders, (2) using a blended approach, combining face-to-face and online elements right from the start of the project and (3) a low-threshold approach with a course duration of two hours. Here we specify the HSN concept and report first results from a sample of 150 students. The participating students completed a self-report questionnaire before and after the course regarding their “confidence to help.” The program demonstrated good feasibility without any relevant side effects. On a descriptive level we observed an improvement of the averaged values of all questionnaire items after the course. These positive initial results merit the further development of HSN as a low-threshold psychological first aid program.